When the culprit lies outside the coronary artery: dual case report of coronary sinus of valsalva dissection presenting as STEMI - Chen, Kun; Yu, Mengjiao; Ling, Youpeng (Frontiers in Cardiovascular Medicine, 2025)
Located sinus of Valsalva (SOV) dissection is a rare but critical condition that presents as inferior ST-segment elevation myocardial infarction (STEMI). We present two cases in which computed tomography angiography (CTA) was essential in identifying SOV dissection. In the first case, CTA confirmed a localized dissection of the right SOV. Surgical revascularization was delayed owing to initial diagnostic challenges and the family's hesitation, which ultimately led to a fatal outcome. In the second, intravascular ultrasound (IVUS) confirmed extrinsic compression of the right coronary artery (RCA), and following emergency stent implantation, coronary blood flow was restored, conservative treatment achieved a favorable clinical outcome. These cases highlight the pivotal role of early CTA when angiographic findings are incongruent with the clinical presentation, the utility of IVUS in determining the etiology of coronary artery occlusion, and the critical importance of timely revascularization.